2021
DOI: 10.1212/wnl.0000000000012068
|View full text |Cite
|
Sign up to set email alerts
|

New Model for Estimation of the Age at Onset in Spinocerebellar Ataxia Type 3

Abstract: ObjectivesThe aim of this study was to develop an appropriate parametric survival model to predict patient's age at onset (AAO) for spinocerebellar ataxia type 3/Machado-Joseph disease (SCA3/MJD) populations from mainland China.MethodsWe compared the efficiency and performance of 6 parametric survival analysis methods (exponential, weibull, log-gaussian, gaussian, log-logistic, and logistic) based on cytosine-adenine-guanine (CAG) repeat length at ATXN3 to predict the probability of AAO in the largest cohort o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…We further observed moderate‐to‐strong associations of cerebellar and pons MR metrics with estimated ataxia duration. Existing statistical models to estimate time to ataxia onset in preataxic individuals utilize CAG repeat length and current age 17,18 . Although they perform well at the group level, these estimates carry a large uncertainty in estimating onset age of individual patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We further observed moderate‐to‐strong associations of cerebellar and pons MR metrics with estimated ataxia duration. Existing statistical models to estimate time to ataxia onset in preataxic individuals utilize CAG repeat length and current age 17,18 . Although they perform well at the group level, these estimates carry a large uncertainty in estimating onset age of individual patients.…”
Section: Discussionmentioning
confidence: 99%
“…Existing statistical models to estimate time to ataxia onset in preataxic individuals utilize CAG repeat length and current age. 17,18 Although they perform well at the group level, these estimates carry a large uncertainty in estimating onset age of individual patients. Noninvasive imaging metrics can enrich these parametric models and are expected to reduce the uncertainty of these estimates, which will be critical in subject stratification in trials.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study attempting to apply XAI to the AAO prediction of SCA3/MJD. This study proposed an XAI model based on feature optimization, which achieved a better AAO prediction accuracy than previous studies (Peng et al, 2021a , b ) and can explain the impact of features and provide a personalized prediction.…”
Section: Discussionmentioning
confidence: 88%
“…The previous piecewise XGBoost model for AAO prediction of SCA3/MJD patients achieves metrics of MAE (5.56 and 4.78), RMSE (7.13 and 6.31), MedianAE (4.15 and 3.59), and proportion < 5 (55% and 65%) for CAGexp ≤ 68 and CAGexp > 68, respectively (Peng et al, 2021a ). Another survival analysis study proposed a parametric survival analysis method to predict the AAO with a reported R 2 of 0.54 (Peng et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation